Health literacy and associated factors among adult type 2 diabetic patients in Woldia Comprehensive Specialized Hospital, North-East Ethiopia, 2022 - Mulugeta Abate, Habtemariam; Kumar, Prem; Anteneah, Samuel; Girma, Mitaw; Yimam, Wondosen; Desu, Birhanu (Frontiers in Public Health, 2025)
BackgroundDespite limited research, health literacy in developing countries like Ethiopia remains low, making it a significant challenge to combat non-communicable diseases.ObjectiveTo assess the level of health literacy and associated factors among adult type 2 diabetic patients in Woldia Comprehensive Specialized Hospital, North-East Ethiopia, 2022.Methods and materialsA cross-sectional study was conducted at Woldia Comprehensive Specialized Hospital from April 19 to July 19, 2022, involving 423 participants. Systematic random sampling, face-to-face interviews, and document reviews were used to collect data. The data were coded and entered into Epi-Data version 4.6.0.2, then analyzed using Statistical Package for the Social Sciences (SPSS) version 26. The results were presented in texts, tables, and figures. Bivariable and multivariable logistic regression analyses were performed to identify significant predictors with p-values below 0.05 and to verify the assumptions of binary logistic regression.ResultGeneral Health Literacy Index was 27.86 (±6.71), and the magnitude of participants with adequate health literacy in the study was 22.2% (95% CI: 18.4–26.3%). Ages (18–35) years [(AOR =14, 95% CI = 3.86–50.77)], ages (36–50) years [(AOR = 15.38, 95% CI = 4.23–55.9)], being male [(AOR = 2.945, 95% CI = 1.570–5.526)], no experiencing depression symptoms [(AOR = 2.673, 95% CI = 1.308–5.463)], not experiencing anxiety [(AOR = 2.001, 95% CI = 1.011–3.960)] and being literate [(AOR = 4.120, 95% CI = 1.397–12.146)] were significantly associated with adequate health Literacy.Conclusion and recommendationsThe magnitude of adequate health literacy was low. Ages (18–35) years, ages (36–50) years, being male, not experiencing depression symptoms, not experiencing anxiety, and being literate were significantly associated with adequate health literacy. Health professionals should regularly implement health education programs for diabetic patients and communities, focusing on females, older adults, the illiterate, and those experiencing depression and anxiety.